2010
DOI: 10.1016/j.neuropsychologia.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Response times for visually guided saccades in persons with Parkinson's disease: A meta-analytic review

Abstract: Individuals with Parkinson's disease (PD) show marked impairments in their ability to generate self-initiated, or "voluntary", saccadic eye movements. Investigations of visually guided, or "reflexive", saccades have, on the other hand, produced inconclusive results with studies showing response times (RTs) in persons with PD that are slower, faster, or indistinguishable from those of controls. We performed a meta-analysis to establish whether there are consistent effects of PD on the metrics of visually guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 71 publications
7
58
0
1
Order By: Relevance
“…Previously, Parkinsonian hypometria has only been found consistently under “open loop” or memory-guided conditions where peripheral target stimuli are not present. Responding in stimulus driven conditions is typically found to be normal or even show evidence for speeding of response latencies under certain conditions in PD (Chambers & Prescott, 2010). The present experiments suggest that hypometria may occur under other conditions where saccades have to be made partially on the basis of internal cognitive representations (in this case learned rules or stimulus response mappings) even when visual markers for responding are provided in the display.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Parkinsonian hypometria has only been found consistently under “open loop” or memory-guided conditions where peripheral target stimuli are not present. Responding in stimulus driven conditions is typically found to be normal or even show evidence for speeding of response latencies under certain conditions in PD (Chambers & Prescott, 2010). The present experiments suggest that hypometria may occur under other conditions where saccades have to be made partially on the basis of internal cognitive representations (in this case learned rules or stimulus response mappings) even when visual markers for responding are provided in the display.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis suggested that the eccentricity of the visual target has a critical effect on PST reaction times in PD. PD patients trigger saccades more rapidly when the target is relatively close to fixation point and more slowly for targets that are more distant (Chambers and Prescott 2010). However, there is a lack of consensus on antisaccades (Lueck et al 1990;Kitagawa et al 1994;Vidailhet et al 1994a;Crevits and DeRidder 1997;Briand et al 2001;Cameron et al 2012).…”
Section: Saccadic Eye Movements In Parkinson's Diseasementioning
confidence: 99%
“…Further, there is even disagreement about whether prosaccade latencies in PD are slower, faster, or indistinguishable (29, 30). There are many variables that have been shown to affect saccade parameters including age (31), dopaminergic medication (24), and disease stage (30, 32).…”
Section: Introductionmentioning
confidence: 99%